Sosialisasi Pentingnya Pengaturan dan Pemanfaatan Aset Desa Untuk Meningkatkan Pendapatan Desa di Desa Lau Kecamatan Dawe Kabupaten Kudus - Kristiyanto Kristiyanto; Lidya Christina Wardhani; Wahyu Edy Amrulloh (Muria Jurnal Layanan Masyarakat, 2020)
Abstract Lau Village in Dawe Subdistrict is one of the villages in Kudus Regency that still does not have clear rules regarding village assets and their use. Therefore, the purpose of this activity is to provide information and knowledge to village officials, BPD, and community representatives about the importance of village assets in Lau Village and how to use them so that existing village assets can help support village income and development. The method used in this activity is the socialization carried out by the team, then followed by a discussion related to obstacles and problems that arise related to village assets and their use so far. The solution offered is to provide information on the proper arrangement of village assets in accordance with the Village Law and the rules below, so that village assets in Lau Village can be in accordance with the law and have legal certainty, as well as with the management and use of village assets that are optimal. Keywords: Regulation, Utilization, Village Assets, Village Income